Nanoformulated rosemary extract impact on oral cancer: in vitro study - Ellithy, Marwa Mohamed (2023)
Rosemary nanoparticles composite characterization Transmission electron microscope (TEM) informed us on the particle shape as well as their size. TEM micrographs of these nanoparticles are shown in Fig. 1. Electron microscopy analysis confirmed the presence of nanoparticles. RE-loaded chitosan nanoparticles were found to be spherical, distinct and regular with a size of 0.5 µm to 200 nm. Their surface is solid and has a dense structure. Chitosan nanoparticles appeared aggregated in the photomicrographs. The RE particles were well coated by chitosan. The particle size of the prepared nanoparticles ranged from 0.5 µm to 200 nm with an average size of 100 nm.